DECOLONIZATION AND ANTIRACIST ACTIVISM WITHIN COACHING PROCESSES THE 8TH EYE - LOOKING THROUGH A POWERFUL BLACK LENS - Paul, Heather (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2021)
This paper aims to contribute to the development of existing and future coaching frameworks. I bring my diverse personal experiences and professional interests in thinking about what decolonizing coaching could entail in terms of anti-racist activism, learning and development. The 8th eye, a decolonizing eye, a powerful Black lens uses critical race theory as an approach. The approach focuses on empowering Black people and People of Colour (BPOC) and Indigenous people experiencing discrimination within their organizations and supports everyone to challenge and change systemic oppressions. Supporting individuals and institutions committed to decolonization and antiracist activism to reflect on existing coaching frameworks. We cannot address the realities of the racism faced by BPOC and Indigenous people with purely Eurocentric lenses and being racism deniers. Therefore, listening to people’s experiential exchanges, shows “over standing[1]” and values different responses. [1] Overstanding is originally Jamaican patois with Rastafarian roots, now part of Black British communities, and means deep understanding.